Assessment of the relation of doctors and patients to development of business in medicine - Ye. A. Rabtsun (Бюллетень сибирской медицины, 2009)
The opinion of doctors and patients on the suitability and forms of business activity in medicine is studied. For most people, free medical aid has not clear boundaries, and this fact significantly reduces the motivation to payment for medical services, that is, restrains the demand. The businessmen’s mentality is not formed as well: in the medical community, a medical service is not realized as a good, and the medical activity is not understood as an activity on production and marketing of medical services, the «kept» psychology dominates. The paying capacity of people should not be considered as a key factor restraining the development of medical business. The more significant problem is that the current medical system is not ready and capable to sell medical services to people having the considerably increased level of consumer demand.